Universal effective hadron dynamics from superconformal algebra - Brodsky, S.; Dosch, Hans Günter; Lorcé, Cédric (Physics letters, 2016)
An effective supersymmetric QCD light-front Hamiltonian for hadrons composed of light quarks, which includes a spin-spin interaction between the hadronic constituents, is constructed by embedding superconformal quantum mechanics into AdS space. A specific breaking of conformal symmetry inside the graded algebra determines a unique effective quark-confining potential for light hadrons, as well as remarkable connections between the meson and baryon spectra. The results are consistent with the empirical features of the light-quark hadron spectra, including a universal mass scale for the slopes of the meson and baryon Regge trajectories and a zero-mass pion in the limit of massless quarks. Our analysis is consistently applied to the excitation spectra of the π, ρ, K, K⁎ and ϕ meson families as well as to the N, Δ, Λ, Σ, Σ⁎, Ξ and Ξ⁎ in the baryon sector. We also predict the existence of tetraquarks which are degenerate in mass with baryons with the same angular momentum. The mass of light hadrons is expressed in a universal and frame-independent decomposition in the semiclassical approximation described here.